CIRCADIAN VARIABILITY AND CIRCADIAN HYPER AMPLITUDE TENSION AS A EARLY PREDICTIVE MARKER OF CHEMOTHERAPHY INDUCED CARDIOTOXICITY. (April 2021) - Bhardwaj, Shipra; Verma, Narsingh; Bhatt, M L B; Rastogi, Madhup
Abstract : Objective: Chemotherapeutic Medicines like Anthracycline antibiotics are effectively being used for breast cancer treatment in India. Despite of close clinical monitoring, the use of serological markers, such as troponins and BNP, and finally by using standard and novel imaging techniques like, nuclear imaging, echocardiograms etc some patients still develop severe left ventricular dysfunction. Also there are certain limitations of these techniques as these techniques can predict CV damages only after Cardiac function deterioration has become irreversible. Design and method: Therefore in this study Seven day continuous ambulatory blood pressure monitoring and CHAT (circadian hyper amplitude tension) have been evaluated to find out the variability in blood pressure and heart rate as a marker for cardiac function. Subjects who were fulfilling the inclusion criteria were enrolled for study. 24 hour /7days Ambulatory blood pressure monitoring, Left ventricular Ejection Fraction ratio (LVEF), Heart rate variability (HRV) and Cardiotoxicity Biomarkers viz Brain Natruitic peptide (BNP) and C- Reactive Protein (Hs CRP) and Troponin T were analyzed before receiving first Cycle of Antracycline Chemotherapy. All the parameters were repeated after first and Second Cycle of Chemotherapy. Results: Results shows significant increase in MESOR and Double Amplitude and Hyperbaric indexes of SBP, DBP and HR after Chemotherapy. Number of subjects diagonosed with CHAT (Circadian Hyper Amplitude Tension) increased after Chemotherapy while No Significant Changes were noted in LVEF (Left Ventricular ejection fraction) and serum biomarkers (i.e Troponin T, Hs CRP, and BNP). These data suggest that Anthracyclines Chemotheraphy treatment in Breast Cancer Subjects produces variations in 7 day circadian pattern of blood pressure and heart rate which can result into disturbed vascular events and thus are at greater risk of cardiovascular morbidity. Conclusions: long term monitoring of circadian pattern of blood pressure and heart rate in cancer patients will be an effective measure to prevent chemotherapy induced cardiotoxicity. Chronobiological screening parameters will be a novel approach in the context of chemotherapy induced cardiotoxity in order to identify or stratify risk in cancer patients that would potentially benefit from early cardio protective or other precautionary measures.